Capacity Building on Modeling the Ethiopian Energy System: Final Workshop - Mondal, Alam; Belete, Alebachew Azezew; Mekonnen, Dawit (2020)
Alam Mondal, Alebachew Azezew Belete, Hua Xie, Dawit Mekonnen WEBINAR Capacity Building on Modeling the Ethiopian Energy System: Final Workshop SEP 30, 2020 - 02:00 PM TO 04:00 PM EAT